Semantic Memory Navigation in Hiv: Conceptual Associations and Word Selection Patterns - Garcia-Serrano, A (Routledge, 2025)
Objective: This proof-of-concept study aimed to characterize semantic memory profiles in individuals with human immunodeficiency virus (HIV) and mild neurocognitive impairment. Method: Using a semantic relatedness task, we explored conceptual association and word selection patterns in people living with HIV (PLWH; n = 50) relative to people living without HIV (n = 46). We also studied whether word selection patterns in the PLWH group were associated with working memory capacity, cognitive flexibility and inhibitory control. Results: While accuracy did not differ between groups, PLWH produced significantly longer responses than controls (r =.32), with fewer hypernyms (d =.47), more troponyms (r =.37), and words that were more frequent (r =.39) and had more phonological neighbors (r =.22). These patterns survived covariation with participants’ cognitive status. None of these patterns correlated with measures of working memory, cognitive flexibility, inhibitory control or viral load (all correlation coefficients <.36). Conclusions: Together, these results suggest that PLWH might use alternative word finding strategies during semantic memory navigation, irrespective of the severity of other cognitive symptoms. Such findings contribute to the characterization of cognitive deficits in HIV and to the search for novel markers of the condition. © 2024 Informa UK Limited, trading as Taylor & Francis Group.